The Use of KWL Strategy on Students' Reading Comprehension - Ardiyan, Rifqi Naufal (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2022)
Reading is a dynamic process of catching the words' meaning and getting the text's information. In reading comprehension, students must engage with their reading to comprehend the text. However, reading interest is still a big problem in Indonesia. This research aims to prove the effectiveness of using KWL strategy on students' reading comprehension. The KWL strategy stands for what I Know, what I Want to learn, and what I did Learn. This research applied a pre-experimental method with one group pre-test and post-test design as the research methodology. The tenth-grade students in SMAN 1 Cisaat are taken as the population of this research. Thirty-five students were selected as the samples using a random sampling technique with the lottery method. The tests were given to measure their reading comprehension ability, and the data were analyzed using the t-test formula. From the calculation, the researcher finds the result of the t-test value is 11.28 with the degree of freedom (df) is 34, and the t-table value at the significant level of 0.05 is 2.042. the result shows that the value of the ttest is higher than t-table 11.28 2.042. it means that the alternative hypothesis (ha) is received. Therefore, the researcher concludes that using the KWL strategy affects students' ability in reading comprehension.